Direct RAPD evaluation of bacteria without conventional DNA extraction - Welington Luiz Araújo; Derlene Attili de Angellis; João Lúcio Azevedo (Brazilian Archives of Biology and Technology, 2004)
The present work reports successful DNA amplification of Pantoea agglomerans and Bacillus pumilus through Random Amplified Polymorphic DNA (RAPD). For this, template DNA was obtained without conventional DNA extraction. The procedure was as follows: cultures grown for 20 hours in 5 mL LB medium were centrifuged and the resulting preparation was suspended in TE buffer. After boiling, the cell suspension was diluted and 2.0 µl were used in reactions of 15 µl. The results showed no significant differences among the RAPD profile of the PCR reactions derived from the boiling and phenol extraction methods, suggesting the utilization of this method for genetic population analysis. O presente trabalho mostra a amplificação de DNA das bactérias Pantoea agglomerans e Bacillus pumilus por meio da técnica de RAPD (Amplificação ao acaso de DNA polimórfico). Para esta análise, o DNA molde foi obtido sem a utilização de técnicas de extração convencional, ou seja, sem a purificação do DNA. Bactérias foram cultivadas por 20 horas em 5 mL de meio LB, centrifugado e ressuspendido em tampão TE. A suspensão resultante foi fervida por 5 min., diluída e 2,0 µL foram usados em reações de 15 µL. Os resultados mostraram que os padrões observados com o DNA obtido pela fervura das células não apresentou diferenças significativas daquele obtido com DNA extraído e purificado com fenol, sugerindo a possibilidade da utilização deste método para o estudo da variabilidade genética de populações microbianas.